REVIEW OF THE TEXTBOOK "HISTORY OF DAGESTAN" OF THE AUTHORS - Dalgat, El'mira Murtuzalievna (History, Archeology and Ethnography of the Caucasus, 2019)
Published last year, the book "History of Dagestan" is a revised and expanded version of the early publications of the author’s team. This is a textbook for teachers, students and students of secondary schools. The book covers the history of Dagestan, from the primitive period to 2010 Shows the economic development of the peoples of Dagestan at different historical stages, social relations, political structure. The most vivid and significant events of struggle of Dagestanis with foreign conquerors are considered. Questions of development of culture of the people of Dagestan are considered.